2016
DOI: 10.3174/ajnr.a4838
|View full text |Cite
|
Sign up to set email alerts
|

High-Convexity Tightness Predicts the Shunt Response in Idiopathic Normal Pressure Hydrocephalus

Abstract: BACKGROUND AND PURPOSE:Although neuroimaging plays an important role in the diagnosis of idiopathic normal pressure hydrocephalus, its predictive value for response to shunt surgery has not been established. The purpose of the current study was to identify neuroimaging markers that predict the shunt response of idiopathic normal pressure hydrocephalus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
97
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(103 citation statements)
references
References 39 publications
4
97
0
2
Order By: Relevance
“…Thus, the presence of high convexity tightness is suggested to be a highly predictive feature of DESH. Previous reports also suggested the importance of high convexity tightness as the most predictive feature of the three components of DESH, for surgical outcomes in terms of Mini-Mental State Examination score, gait disturbance, and the total scoring [19]. Another study also reported that high convexity tightness combined with ventriculomegaly was a predictor for shunt effectiveness in patients with suspected iNPH [27].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Thus, the presence of high convexity tightness is suggested to be a highly predictive feature of DESH. Previous reports also suggested the importance of high convexity tightness as the most predictive feature of the three components of DESH, for surgical outcomes in terms of Mini-Mental State Examination score, gait disturbance, and the total scoring [19]. Another study also reported that high convexity tightness combined with ventriculomegaly was a predictor for shunt effectiveness in patients with suspected iNPH [27].…”
Section: Discussionmentioning
confidence: 88%
“…In other words, most of the subjects with high convexity tightness also presented with Sylvian dilatation as well as ventriculomegaly. In addition, although both Sylvian dilatation and ventriculomegaly are morphologic features of hydrocephalus, these are also observed in brain atrophy [19]. Thus, the presence of high convexity tightness is suggested to be a highly predictive feature of DESH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the treatment of NPH relies partly on accurate neuroimaging diagnosis and characterization. 10,11 Kitagaki et al 9 demonstrated that the Sylvian fissure CSF volume and ventricular volume were greater in patients with iNPH compared with other dementias (ie, Alzheimer disease). Patients with iNPH also had decreased CSF in the superior convexity and medial subarachnoid spaces.…”
Section: Discussionmentioning
confidence: 99%
“…However, morphological signs of iNPH and their relation to symptoms have rarely been described in the general population [8]. Most previous studies have described morphological changes of iNPH on computed tomography (CT) or magnetic resonance imaging (MRI) in patients selected for shunt surgery, with the focus on predicting shunt response [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%